Prevalence of Obesity and Overweight among School-Aged Children in Saudi Arabia and Its Association with Vitamin D Status: Prevalence of Obesity in School Children - Al Shaikh, Adnan; Farahat, Fayssal; Abaalkhail, Bahaa; Kaddam, Ibrahim; Aseri, Khalid; Al Saleh, Yousef; Al Qarni, Ali; Al Shuaibi, Ahmed; Tamimi, Waleed (Acta Biomedica Atenei Parmensis, 2020)
Background: Childhood obesity is a significant global public health problem. Worldwide data showed an increasing trend over the years. We aimed to explore the prevalence of obesity, and its association with vitamin D status. Methods: This cross-sectional study was conducted during the period from 2016 to 2017. The study included 3613 schoolchildren aged 6-19 years in the western, central, and eastern regions in Saudi Arabia. Anthropometric data including age, sex and body mass index (BMI) was collected and the serum 25OH- vitamin D (25OHD) was measured. Age-sex standardized BMI Z-scores using the 2007 World Health Organization growth standards were applied. Results: Data from 3613 school-aged children (females = 51.8%), with equal percentage of participants from each region were analyzed. Prevalence of obesity and overweight was estimated at 7.1% and 14.4% respectively. An increasing trend was detected with age (p: 0.006). Obesity started to increase at the age of 10 years and continued to increase until 19 years. Most of the obese children (64.2%) had deficient vitamin D levels, compared to 33.7% of them with suboptimal levels and only 2.0% with optimal levels (p: